(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of a jail sentence in criminal law is to serve as a deterrent to the convicted criminal.An offender receives punished so that they may be rehabilitated and given a second chance at life insociety in order to recoup the benefits of their criminal behaviour. In spite of the fact that there are nointernationally agreed-upon standards for reporting recidivism, the rate of recidivism among criminalshas been rising worldwide, and India gives a severely distorted image of that rate. Because of thefundamental role that incarceration plays in defining an offender’s trajectory and potential responses,research on recidivism and its connections to incarceration is essential. This article aims to objectivelyexamine the global trends of repeat offenders, their motivations for reoffending, the degree to whichthese factors are linked, and what can be done to reduce recidivism everywhere. It will also examinesome successful approaches used in other countries.